MUSYAWARAH GURU MATA PELAJARAN (MGMP) AND ISLAMIC RELIGIOUS EDUCATION TEACHER DEVELOPMENT: AN EFFORT TO IMPROVE THE QUALITY OF LEARNING - Daruri, Daruri; Ulfiah, Ulfiah; Muchtar, Hendi S.; Mudrikah, Achmad (Universitas Pendidikan Indonesia, 2022)
Abstract. This research is motivated by the low of competence of Pendidikan Agama Islam (Islamic Religious Education, PAI) teachers in implementing a qualified learning of PAI, so the role of supervisors is questionable. The purpose of this study is to describe how the supervisor’s strategy in fostering PAI teachers in improving the quality of learning through MGMP empowerment. A qualitative approach with interviews, observations, and documentation was used to explore data on PAI teachers in the city of Bandung. The results of the study found that the Musyawarah Guru Mata Pelajaran (Subject Teacher Meetings, MGMP) strategy emphasized on six competencies that must be possessed by PAI teachers through activities in MGMP has been running well, directed, clear, and sustainable, but clear and firm regulations are needed regarding MGMP organizational governance and the competence of supervisors in coaching teachers should be strengtened.